The antecedents of transparency of Italian public entities: An empirical analysis in universities and public research institutes - Angela Rella; Arcangelo Marrone; Nicola Raimo; Filippo Vitolla (Administrative Sciences, 2022)
Transparency within universities and public research institutes is an element of significant relevance in the Italian context. Over the years, the need for greater transparency has prompted the legislator to regulate transparency obligations in order to ensure a minimum level of information disclosure. Despite the normative obligation, Italian universities and public research institutes provide different levels of information. This circumstance requires an empirical analysis aimed at understanding the different levels of transparency of Italian universities and public research institutes, and the factors that can influence the amount of information disclosed. The results show a positive impact of the size and the internationalization on the level of the transparency of these institutions.
Keywords: 350; information disclosure; public administration; public research institutes; transparency; universities